Da'wah Communication and Economic Empowerment of Muslims: Opportunities, Challenges, and Strategies - Rahmatunnair, Rahmatunnair; A, Saripah (State Islamic Institute of Bone, Indonesia, 2023)
Da’wah communication is one of the forums for empowering the economy of Muslims in which it entrusts the delivery of da’wah communication loaded with normative theological messages that are able to direct Muslims to economic behavior colored by Islamic values. In its implementation, da’wah communication and economic empowering of Muslims have constructive relations that strengthen each other. The opportunity for da’wah communication in empowering the economy of Muslims is the existence of theological awareness that is rooted in the social life system of Muslims and the normativity of values that regulate the pattern of attitudes and economic behavior of Muslims. The challenges in this process are the increasing demands of profane, hedonistic, and pragmatic life and increasingly fierce economic competition amid limited sources of income. In its empowering, there are several strategies that can be done, namely empowering da’wah communication in the transformative locus of fiqh al-iqtishad and empowering relations between da’wah bi al-lisan, da’wah bi al-hal, and da’wah bi al-siyasah